2019
DOI: 10.1007/s12264-019-00411-7
|View full text |Cite
|
Sign up to set email alerts
|

Hes1 Knockdown Exacerbates Ischemic Stroke Following tMCAO by Increasing ER Stress-Dependent Apoptosis via the PERK/eIF2α/ATF4/CHOP Signaling Pathway

Abstract: Apoptosis induced by endoplasmic reticulum (ER) stress plays a crucial role in mediating brain damage after ischemic stroke. Recently, Hes1 (hairy and enhancer of split 1) has been implicated in the regulation of ER stress, but whether it plays a functional role after ischemic stroke and the underlying mechanism remain unclear. In this study, using a mouse model of ischemic stroke via transient middle cerebral artery occlusion (tMCAO), we found that Hes1 was induced following brain injury, and that siRNA-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Excessive ER stress induces neuronal apoptosis, and in turn aggravates neuronal damage caused by cerebral ischemia [32]. Under this circumstance, GRP78 acts as a sensor and activates PERK and IRE1α, after which downstream signaling molecules such as eIF2α, ATF4, and CHOP are activated [33]. In the present study, we established an OGD cellular model and found that GRP78 was up-regulated at the early stage of hypoxia (3 h) and continued to increase in a time-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ER stress induces neuronal apoptosis, and in turn aggravates neuronal damage caused by cerebral ischemia [32]. Under this circumstance, GRP78 acts as a sensor and activates PERK and IRE1α, after which downstream signaling molecules such as eIF2α, ATF4, and CHOP are activated [33]. In the present study, we established an OGD cellular model and found that GRP78 was up-regulated at the early stage of hypoxia (3 h) and continued to increase in a time-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged environmental stress triggers signal transduction pathways that lead to apoptosis and thereby heighten pathological processes, leading to cerebral damage (Chi et al, 2019 ). Endoplasmic reticulum stress exerts its vital role in stroke-induced neural apoptosis (Mohammed Thangameeran et al, 2020 ) through activation of downstream CCAATenhancer-binding protein homologous protein (CHOP) and caspase-12 (Chi et al, 2019 ; Chu et al, 2019 ; Li Y. et al, 2020 ). SIRT1 is a nicotine adenine dinucleotide (NAD+)-dependent enzyme that deacetylates numerous transcription factors in response to ischemic stress and is involved in various biological pathways (Chen et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The time window of mechanical thrombectomy is only 6 h and is not sufficient. The timely restoration of blood flow results in oxidative stress, inflammatory responses, and endoplasmic reticulum stress [8][9][10]. Therefore, it is crucial to find a way to avoid or attenuate cerebral ischemia-reperfusion injury to improve treatment of ischemia stroke.…”
Section: Introductionmentioning
confidence: 99%